Ultrasound Study to Validate the Anterior Cervical Approach to the Longus Colli Muscle Using Electromyography Control Alone. (29th September 2020) - Hicklin, Lucy A.; Kocer, Serdar; Watson, Natalie A.; Marion, Marie-Helene
Background: One of the main difficulties in the treatment of dystonic anterocollis is the injection of the deep flexor muscles of the neck such as Longus Colli (LCo). The injection of the LCo has been regarded as difficult and potentially dangerous; since we published our anterior median approach, a number of questions about the precision and the safety of our technique have been raised by colleagues. Methods: 7 patients with anterocollis were injected, using our injection technique and when the needle was deemed to be in place, we used the ultrasound probe to determine what the needle had passed through, the depth of the tip of the needle and if the identified muscle was indeed LCo. Results: On the ultrasound section the LCo muscle is between 24 and 28 mm deep in the patients examined in this study. The location of the needle was confirmed by ultrasound and in most cases the needle was placed in the right axis but sometimes not deep enough. The EMG control made it possible to correct the depth in all cases. In most of the injections the needle traversed the thyroid. No acute incident occurred by this route of injection. Injections were performed between 22 and 28 mm deep. Discussion: From this study and based on a review of complications over 9 years experience with injecting LCo under EMG control using an anterior approach, we conclude that this technique is precise, safe and well tolerated. Summary (Highlights): The injection of the Longus Coli muscle for anterocollis has been regarded as difficult and potentially dangerous. This study showed, using ultrasound to determine the needle trajectory, that the anterior approach using EMG control is a precise, safe and well tolerated technique.